Case report on irritational fibroma - Anishka Dhanai; Hiroj S Bagde; Radhika Gera; Koushik Mukherjee; Chandni Ghildiyal; Hemlata Yadav (Wolters Kluwer Medknow Publications, 2024)
Traumatic or irritation fibroma is the healed end product of the inflammatory hyperplastic lesion, which can occur at any age from almost any softtissue site, tongue, gingiva, and buccal mucosa being the most common. It is usually characterized by a slow, painless growth accumulated over a period of months or years.